A Descriptive Study of 100 Patients Undergoing Palliative Nerve Blocks for Chronic Intractable Headache and Neck Ache - Peter Rothbart; Katherine Fiedler; George D Gale; David Nussbaum; Nelson Hendlerb (Pain Research and Management)
OBJECTIVE: To ascertain whether repeated (palliative) nerve blocks over a long period of time provide benefit to patients with chronic intractable headache and neck ache.